Listening as a Second Language Listening Comprehesion - Zanah, Siti Nur; Santoso, Didik (Yayasan Daarul Huda Kruengmane, 2024)
The aim of this research is to define Listening as Second Language Listening Comprehension. The author chose the English Language Education Program, semester 1 of the North Sumatra State Islamic University, class TBI 4 with a total of 7 students out of a total of 30 students. Data collection through questionnaire surveys. The seven sample students were asked questions about listening comprehension, what materials can help them improve their language skills, such as music, then factors that influence whether they receive listening comprehension quickly or slowly, such as age, gender and learning style. The results of the research and analysis show that the seven students who answered the questionnaire had different understandings regarding listening comprehension, however, as explained by Mehrpour and Motlagh (2015), there are factors that influence the speed of understanding a second language, in the form of age, learning style and gender.